A shovel for garden maintenance - YIN CHUANSONG (2018)
The utility model discloses a shovel for garden maintenance, include the handle and hold the case, holding the incasement and placing a plurality of not unidimensional shovel heads, the top of each shovel head has an organic whole and is provided with mutually unidimensional first connector, the end fixing of handle has the second connector with first connector detachably matched, the top that holds the case be provided with with second connector complex third connector, the third connector is for having the internal screw thread sleeve pipe, be provided with on the outer wall of second connector with casing thread complex thread head. The utility model has the characteristics of the application is strong. 本实用新型公开了种用于园林维护的铁铲，包括手柄和容纳箱，所述容纳箱内放置有若干不同尺寸的铲头，每个铲头的顶部具有体设置有相同尺寸的第连接头；所述手柄的端部固定有与第连接头可拆卸配合的第二连接头；所述容纳箱的顶部设置有与第二连接头配合的第三连接头；所述第三连接头为带有内螺纹的套管；所述第二连接头的外壁上设置有与套管螺纹配合的螺纹头。本实用新型具有应用性强的特点。